Structural testing of compression members reinforced with FRP bars - Maria Włodarczyk (Archives of Civil Engineering)
The Fibre Reinforced Polymer (FRP) bars are increasingly used as an alternative to steel reinforcement in concrete structures. Their wide applicability is due to their properties such as high strength, resistance to corrosion, easy cutting, etc. For many years, research has been conducted on the identification of properties and the possibility of application of FRP bars in structural members as the alternative to steel reinforcement. This paper presents results of experimental tests of concrete columns reinforced with BFRP (Basalt Fibre Reinforced Polymer) and HFRP (Hybrid Fibre Reinforced Polymer) bars. Observed failure modes are presented along with comparison of the experimental and the predicted ultimate capacities of the regarded columns.